Prospective Associations Between Preschool Exposure to Violent Televiewing and Psychosocial and Academic Risks in Early Adolescent Boys and Girls. Issue 1 (2nd January 2023) - Pagani, Linda S.; Bernard, Jessica; Fitzpatrick, Caroline
Abstract : This article has supplementary material on the web site: www.jdbp.org . ABSTRACT: Objective: Risks of early exposure to media violence remain unclear. This study examines typical early childhood violent media exposure and subsequent psychosocial and academic risks. Methods: Our longitudinal birth cohort comprised 978 girls and 998 boys. Child-reported and teacher-reported measures of adjustment at age 12 years were linearly regressed on parent-reported televised violence exposure at ages 3.5 and 4.5 years while adjusting for individual/family confounders. Results: For girls, preschool violent televiewing was associated with increases in emotional distress (b = 0.31; 95% confidence interval [CI], 0.13–0.49) and decreases in classroom engagement (b = −0.97; 95% CI, −1.55 to −0.40), academic achievement (b = −2.60; 95% CI, −3.48 to −1.72), and academic motivation (b = −0.58; 95% CI, −1.09 to −0.07) at age 12 years. For boys, preschool violent televiewing was associated with increases in emotionally distressed (b = 0.33; 95% CI, 0.13–0.53), inattentive (b = 0.25; 95% CI, 0.06–0.45), conduct disordered (b = 0.11; 95% CI, 0.00–0.21), and socially withdrawn behavior (b = 0.23; 95% CI, 0.05–0.40), as well as decreases in classroom engagement (b = −0.84; 95% CI, −1.57 to −0.12), academic achievement (b = −1.19; 95% CI, −2.15 to −0.23), and academic motivation (b = −0.58; 95% CI, −1.13 to −0.03) at age 12 years. Conclusion: Compared with no preschool exposure, violent televiewing is associated with distinct and enduring psychosocial risks by early adolescence. Acknowledging such risks remains a pertinent health literacy target for pediatric professionals, parents, and communities.